Applying the Aboveground-Belowground Interaction Concept in Agriculture: Spatio-Temporal Scales Matter - Veen, G. F.; Wubs, E. R. Jasper; Bardgett, Richard D.; Barrios, Edmundo; Bradford, Mark A.; Carvalho, Sabrina; De Deyn, Gerlinde B.; de Vries, Franciska T.; Giller, Ken E.; Kleijn, David; Landis, Douglas A.; Rossing, Walter A. H.; et al. (Frontiers in Ecology and Evolution, 2019)
Interactions between aboveground and belowground organisms are important drivers of plant growth and performance in natural ecosystems. Making practical use of such above-belowground biotic interactions offers important opportunities for enhancing the sustainability of agriculture, as it could favor crop growth, nutrient supply, and defense against biotic and abiotic stresses. However, the operation of above- and belowground organisms at different spatial and temporal scales provides important challenges for application in agriculture. Aboveground organisms, such as herbivores and pollinators, operate at spatial scales that exceed individual fields and are highly variable in abundance within growing seasons. In contrast, pathogenic, symbiotic, and decomposer soil biota operate at more localized spatial scales from individual plants to patches of square meters, however, they generate legacy effects on plant performance that may last from single to multiple years. The challenge is to promote pollinators and suppress pests at the landscape and field scale, while creating positive legacy effects of local plant-soil interactions for next generations of plants. Here, we explore the possibilities to improve utilization of above-belowground interactions in agro-ecosystems by considering spatio-temporal scales at which aboveground and belowground organisms operate. We identified that successful integration of above-belowground biotic interactions initially requires developing crop rotations and intercropping systems that create positive local soil legacy effects for neighboring as well subsequent crops. These configurations may then be used as building blocks to design landscapes that accommodate beneficial aboveground communities with respect to their required resources. For successful adoption of above-belowground interactions in agriculture there is a need for context-specific solutions, as well as sound socio-economic embedding.